Differential Harnack estimates for the semilinear parabolic equation with three exponents on $ \mathbb{R}^{n} $ - Fanqi Zeng; Wenli Geng; Ke An Liu; Boya Wang (Electronic Research Archive)
In this paper, we thought about the positive solutions to the semilinear parabolic equation with three exponents, and obtained several differential Harnack estimates of the positive solutions to the equation. As applications of the main theorems, we found blow-up solutions for the equation and classical Harnack inequalities. Our results generalize some recent works in this direction.